Participatory Budget: a review of scientific research and its democratic implications from 2000 to 2016 - Buele Nugra, Irene Gisel; Vidueira Mera, Pablo (Universidad Politécnica Salesiana (Ecuador), 2018)
Since the 1900s, a new form of democracy has emerged, where the social representation is reinforced and the citizens participate in the public policy and they determine the budget for their location. The level of diffusion and application of participatory budgeting is unknown. The implications caused for democratic processes are also unknown. In this context, a systematic literature review of publications indexed from 2000 to 2016 was conducted. Using the software NVivo for qualitative analysis and using matrices the following information was organized, analyzed and synthesized: title, author, year of publi-cation, research line and application of common themes. The results show to Porto Alegre in Brazil as the area of greatest application of this methodology, the political will as the main factor of success, and a time of controversy in the process.